Peningkatan Pengetahuan Tukang tentang Struktur Atas Rumah Sederhana Ramah Gempa - Suci Putri Elza; Resmi Bestari Muin (Pusat Riset dan Inovasi Nasional, 2025)
Many simple houses in Indonesia, particularly in Menes District and its surroundings, Pandeglang Regency, are built without considering earthquake resistance principles. This is a serious problem considering that the region is prone to disasters, making the vulnerability of the buildings potentially pose a significant risk to the safety of occupants. One aspect that is often overlooked is the superstructure construction, which plays a crucial role in maintaining the overall stability of the building. Weaknesses in this section can cause severe damage and even collapse during an earthquake. This situation is exacerbated by the lack of knowledge and skills of builders regarding earthquake-resistant housing concepts and a lack of access to standard technical guidelines. To address this issue, this community service program was designed to improve the understanding and skills of builders in building earthquake-resistant simple house superstructures. The activities were carried out through a combination of theoretical and practical training covering the basic principles of earthquake resistance, appropriate material selection, and construction techniques that comply with building safety standards. This training is a collaboration between Mercu Buana University and PT. Tunas Engineering, ensuring that the approach provided is more applicable and relevant to real-world needs. The targeted program outputs include a significant increase in the level of understanding of the craftsmen as measured through pre- and post-training evaluations, the development of a simple training module as a work guide, and the formation of a community of craftsmen who care about earthquake-resistant construction.